Polyamide composite material as well as preparation method and application thereof
By adding specific contents of polyvinylpyrrolidone and polyethylene glycol to the polyamide composite material, the surface energy of the material is improved, the problem of poor screen printing effect of traditional polyamide materials is solved, and better screen printing effect and material performance are achieved.
Patent Information
- Application Number
- CN202411961772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional polyamide materials have poor screen printing effects and are difficult to meet specific needs.
By adding a specific content of polyvinylpyrrolidone and polyethylene glycol with polyamide resin, glass fiber and flame retardant, the surface energy of the polyamide composite material is improved, thereby improving the silk screen printing ability.
A high-surface energy polyamide composite material has been obtained, which significantly improves the silk screening effect and can meet the requirements of the automotive, electronic and electrical industries for material performance.
Smart Images

Figure BDA0005217347350000081 
Figure BDA0005217347350000082 
Figure BDA0005217347350000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics, and specifically relates to a polyamide composite material and a preparation method and application thereof. Background Art
[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeated amide groups on the main chain of the molecule. It can be used as both fiber and engineering plastic. Nylon is the earliest developed synthetic fiber with good comprehensive properties, such as high strength, good rigidity, impact resistance, oil and chemical resistance, wear resistance and good self-lubrication. In addition, the raw materials are easily available and the cost is low. Therefore, it is widely used in industries, clothing, automobiles, electronic appliances, rail transportation and other fields. Nylon materials reinforced with glass fiber and flame retardant modified have higher mechanical strength, better flame retardancy and wider application, especially in the field of electronic appliances, and can replace some metals and other thermoplastic engineering plastics.
[0003] Usually, nylon materials need to be screen printed to meet specific needs, such as marking the material. However, the screen printing effect of traditional nylon materials is poor.
[0004] Therefore, developing a polyamide composite material with good screen printing effect is a problem to be solved urgently in the field. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a polyamide composite material and a preparation method and application thereof. The polyamide composite material has high surface energy and solves the problem of poor silk screen printing of traditional polyamide materials.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a polyamide composite material, which comprises, by weight, 20 to 60 parts of polyamide resin, 8 to 25 parts of polyvinyl pyrrolidone, 0.5 to 3 parts of polyethylene glycol, 15 to 40 parts of glass fiber and 17 to 40 parts of flame retardant.
[0008] In the present invention, the polyamide composite material is added with polyvinyl pyrrolidone and polyethylene glycol, and the two are compounded in specific contents, which is beneficial to improving the surface energy of the polyamide material, thereby improving the screen printing ability of the polyamide composite material.
[0009] In the present invention, the polyamide resin is 20 to 60 parts, for example, it can be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts and the range between any of the above values, preferably 25 to 58 parts, more preferably 30 to 55 parts.
[0010] In the present invention, the amount of polyvinyl pyrrolidone is 8 to 25 parts, for example, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts, 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts, 20 parts, 20.5 parts, 21 parts, 21.5 parts, 22 parts, 23 parts, 24 parts, 25 parts or the range between any of the above values, preferably 12 to 21 parts, more preferably 18.5 to 20.5 parts.
[0011] In the present invention, the polyethylene glycol is 0.5 to 3 parts, for example, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0. .98 parts, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts, 3 parts or a range between any of the above values; preferably 0.8 to 2.5 parts, more preferably 1 to 2 parts.
[0012] In the present invention, the glass fiber is 15 to 40 parts, for example, it can be 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts, 40 parts or any range between the above values; preferably 20 to 30 parts.
[0013] In the present invention, the flame retardant is 17 to 40 parts, for example, it can be 17 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts, 40 parts or any range between the above values; preferably 20 to 30 parts.
[0014] Preferably, the polyamide resin includes at least one of a condensation product of a diamine and a dibasic acid, a condensation product of an aminocarboxylic acid, or a ring-opening polymerization product of a cyclic lactam.
[0015] Preferably, the polyamide resin comprises polyhexamethylene adipamide and / or polycaprolactam, more preferably polyhexamethylene adipamide.
[0016] Preferably, the relative viscosity of the polyamide resin is 2.0 to 3.4, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4 or any range between the above values.
[0017] In the present invention, the relative viscosity of the polyamide resin is the relative viscosity of the polyamide resin with a concentration of 1 g / mL in 96% concentrated sulfuric acid at 25°C. The specific testing method includes: weighing 0.5 g of the polyamide resin, transferring it to a 50 mL volumetric flask, adding about 40 mL of 96% concentrated sulfuric acid by mass, ultrasonically oscillating until the polyamide resin is completely dissolved, cooling the solution to 25°C, diluting it to the scale with concentrated sulfuric acid, and mixing it evenly, testing the flow time of 0.01 g / mL of the polyamide resin solution through the Ubbelohde viscometer at 25°C, recorded as t1, using the same viscometer to test the flow time of the solvent concentrated sulfuric acid, recorded as t2, and t1 / t2 is the relative viscosity.
[0018] Preferably, the melting point of the polyvinyl pyrrolidone is 110-180°C, for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or any range between the above values.
[0019] In the present invention, the K value of the polyvinyl pyrrolidone is 75-115, for example, it can be 75, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 100, 102, 104, 106, 108, 110, 112, 114, 115 or the range between any of the above values; more preferably, it is 85-105.
[0020] Preferably, the number average molecular weight of the polyethylene glycol is 3500 to 12000, for example, 3500, 3600, 3800, 4000, 4200, 4500, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9800, 10000, 10200, 10500, 10800, 11000, 11200, 11500, 11800, 12000 or a range between any of the above values; more preferably 7500 to 11000, and more preferably 8500 to 10500.
[0021] Preferably, the glass fiber includes at least one of alkali-free glass fiber (E glass fiber), high alkali glass fiber (A glass fiber), special glass fiber (S glass fiber), D glass fiber, medium alkali glass fiber (C glass fiber) or quartz glass fiber; preferably alkali-free glass fiber.
[0022] Preferably, the flame retardant includes 13 to 30 parts of an organic phosphinate flame retardant (for example, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or any range between the above values, more preferably 15 to 25 parts) and 4 to 10 parts of a synergistic flame retardant (for example, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or any range between the above values, more preferably 4.5 to 8.5 parts) by weight.
[0023] Preferably, the organic phosphinate flame retardant comprises aluminum diethylphosphinate.
[0024] Preferably, the synergistic flame retardant comprises a melamine flame retardant and / or zinc borate.
[0025] Preferably, the melamine flame retardant includes at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate or melamine zinc polyphosphate, more preferably melamine polyphosphate.
[0026] Preferably, the polyamide composite material further comprises 0.1 to 10 parts of other additives by weight, for example, 0.1, 0.2, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 parts or a range between any of the above values.
[0027] Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a heat stabilizer.
[0028] In the present invention, the antioxidant comprises at least one of a hindered phenol antioxidant, an amine antioxidant, a cuprous halide composite antioxidant or a benzophenone antioxidant.
[0029] In the present invention, the lubricant includes at least one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants or metal soap lubricants; preferably an ester lubricant, such as fatty acid esters, polyol esters, polyethylene glycol esters, etc.
[0030] In the present invention, the heat stabilizer includes a phosphite heat stabilizer; the structural formula of the phosphite heat stabilizer is P(OR)3, wherein R is the same or different and is independently selected from any one of a C1-C20 alkyl group, a C3-C22 alkenyl group, a C6-C40 cycloalkyl group, a C7-C40 cycloalkylene group, a substituted or unsubstituted aryl group; the substituted substituent includes an alkyl group containing at least one carbon atom.
[0031] In the present invention, the other additives include 0.1 to 1 parts of antioxidants and 0.2 to 1.2 parts of lubricants, calculated by weight.
[0032] In a second aspect, the present invention provides a method for preparing the polyamide composite material according to the first aspect, the preparation method comprising the following steps:
[0033] The components are mixed and extruded to obtain the polyamide composite material.
[0034] Preferably, the mixed material further comprises other auxiliary agents.
[0035] In the present invention, the mixing comprises: mixing polyamide resin, polyvinyl pyrrolidone, polyethylene glycol and flame retardant and other optional additives in a high-speed mixer for 3 to 10 minutes, and then adding them to the main feeding hopper of a twin-screw extruder; adding glass fiber to the side feeding hopper of the twin-screw extruder for mixing.
[0036] Preferably, the extrusion temperature is 160-260°C, for example, it can be 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C or a range between any of the above values.
[0037] In the present invention, the screw speed of the twin-screw extruder is 300-800 rpm, the aspect ratio is 36:1-48:1, the barrel temperature of each section of the twin-screw extruder is 160°C-250°C, and the head temperature is 230°C-260°C.
[0038] In a third aspect, the present invention provides a screen printing material, wherein the screen printing material comprises the polyamide composite material described in the first aspect.
[0039] In the present invention, the polyamide composite material has excellent screen printing performance and high impact strength, and can meet the requirements of the automotive, electronic and electrical, connector, energy storage and other industries for material performance.
[0040] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The polyamide composite material provided by the present invention is compounded with polyamide resin, glass fiber and flame retardant by adding specific amounts of polyvinyl pyrrolidone and polyethylene glycol. The obtained glass fiber reinforced and flame retardant modified polyamide composite material has high surface energy and good screen printing ability, and can meet the requirements of automobile, electronic appliances, connectors, energy storage and other industries for material performance. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] The materials used in the present invention can be obtained by commercially available or conventional methods. Unless otherwise specified, the materials used in the present invention are as follows:
[0045] Polyhexamethylene adipamide: nylon 66 (PA66), Shenma Group EPR24, relative viscosity 2.4;
[0046] Polycaprolactam: nylon 6 (PA6), Jiangsu Haiyang Chemical Fiber HY-2800A, relative viscosity 2.75;
[0047] Aluminum diethylphosphinate: Clariant Exolit OP 1230;
[0048] Synergistic flame retardant: melamine polyphosphate, Budit 3141;
[0049] Glass fiber: China Jushi Co., Ltd. ECS10-03-568H;
[0050] Polyvinylpyrrolidone (PVP)
[0051] PVP-1: PVPK90 from Beijing Solable Technology Co., Ltd.;
[0052] PVP-2: Gobekie's PVPK85;
[0053] PVP-3: Gobekie's PVPPK100;
[0054] PVP-4: Gobekie's PVPK80;
[0055] PVP-5: Gobekie's PVPPK110;
[0056] Polyethylene glycol (PEG)
[0057] PEG-1: number average molecular weight is 4000, PEG-4000, Guangzhou Jinchangsheng Technology Co., Ltd.;
[0058] PEG-2: number average molecular weight is 8000, PEG-8000, Guangzhou Fengtian Chemical Co., Ltd.;
[0059] PEG-3: number average molecular weight is 10000, PEG-10000, Guangzhou Rongda Chemical Company;
[0060] PEG-4: number average molecular weight is 12000, PEG-12000, Zeye Biotechnology;
[0061] Antioxidant: Hindered phenol antioxidant, IRGANOX 1098 from BASF;
[0062] Lubricant: ester lubricant, Struktol's TR044W;
[0063] Glycerol: molecular weight 92.09, Jiangsu Runfeng Synthetic Technology Co., Ltd.
[0064] Examples 1 to 20, Comparative Examples 1 to 8
[0065] Embodiments 1 to 20 and comparative examples 1 to 8 respectively provide a polyamide composite material, in parts by weight, the formula of the polyamide composite material is as shown in Tables 1 to 4, wherein " / " indicates that the component is not included in the formula; the preparation method of the polyamide composite material comprises: mixing the components except the glass fiber in a high mixer for 6 minutes, and then adding them to the main feeding hopper of a twin-screw extruder; adding the glass fiber to the side feeding hopper of the sixth section of the twin-screw extruder, fully plasticizing, melting, extruding, drawing, cooling, and pelletizing in the twin-screw extruder to obtain the polyamide composite material. Wherein, the screw speed of the twin-screw extruder is 500rpm, the aspect ratio is 44:1, the temperature of each section of the extruder is 180℃, and the head temperature is 240℃.
[0066] Table 1
[0067]
[0068] Table 2
[0069]
[0070]
[0071] Table 3
[0072]
[0073] Table 4
[0074]
[0075]
[0076] Performance Testing
[0077] (1) Surface energy: The contact angles of the polyamide composite materials provided in Examples 1 to 20 and Comparative Examples 1 to 8 were tested using a contact angle tester, and the surface energy of the polyamide composite materials was calculated using the Fowkes model; the liquid used in the test was water; the larger the surface energy, the better the screen printing ability.
[0078] (2) Screen printing capability: The polyamide composite materials provided in Examples 1 to 20 and Comparative Examples 1 to 8 were screen printed using ink (FBS series-PAHS ink, gold silicon plastic new material). The screen printing effects of the materials were visually observed and divided into three grades, namely A, B, and C. A means excellent, with good gloss after screen printing, smooth surface and no defects; B means good, with no defects and smooth surface after screen printing, but poor gloss; C means unqualified, with defects on the surface after screen printing (such as pores, cracks, etc.), poor gloss, and rough surface.
[0079] The specific test results are shown in Table 5.
[0080] Table 5
[0081]
[0082]
[0083] As can be seen from Table 5, the polyamide composite material provided by the present invention is compounded with polyamide resin, glass fiber and flame retardant by adding specific amounts of polyvinyl pyrrolidone and polyethylene glycol. The obtained glass fiber reinforced and flame retardant modified polyamide composite material has high surface energy and good screen printing ability, the surface energy is ≥27.5mN / m, and the screen printing effect is good.
[0084] It can be seen from the comparative example that the polyamide composite material, which is not compounded with a specific content of polyvinyl pyrrolidone and a specific content of polyethylene glycol, has a reduced surface energy and a poor screen printing effect.
[0085] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyamide composite material, characterized in that: In parts by weight, the polyamide composite material comprises 20 to 60 parts of polyamide resin, 8 to 25 parts of polyvinyl pyrrolidone, 0.5 to 3 parts of polyethylene glycol, 15 to 40 parts of glass fiber and 17 to 40 parts of flame retardant.
2. The polyamide composite material according to claim 1, characterized in that: The polyamide resin includes at least one of a condensation product of a diamine and a dibasic acid, a condensation product of an aminocarboxylic acid, or a ring-opening polymerization product of a cyclic lactam; Preferably, the polyamide resin comprises polyhexamethylene adipamide and / or polycaprolactam, more preferably polyhexamethylene adipamide; Preferably, the relative viscosity of the polyamide resin is 2.0-3.
4.
3. The polyamide composite material according to claim 1 or 2, characterized in that: The K value of the polyvinyl pyrrolidone is 75-115, and more preferably 85-105.
4. The polyamide composite material according to any one of claims 1 to 3, characterized in that: The number average molecular weight of the polyethylene glycol is 3500-12500, preferably 7500-11000.
5. The polyamide composite material according to any one of claims 1 to 4, characterized in that: The glass fiber includes at least one of alkali-free glass fiber, high-alkali glass fiber, special glass fiber, D glass fiber, medium-alkali glass fiber or quartz glass fiber; preferably alkali-free glass fiber.
6. The polyamide composite material according to any one of claims 1 to 5, characterized in that: In parts by weight, the flame retardant comprises 13 to 30 parts of an organic phosphinate flame retardant and 4 to 10 parts of a synergistic flame retardant; Preferably, the organic phosphinate flame retardant comprises aluminum diethylphosphinate; Preferably, the synergistic flame retardant comprises melamine flame retardant and / or zinc borate; Preferably, the melamine flame retardant includes at least one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate or melamine zinc polyphosphate, more preferably melamine polyphosphate.
7. The polyamide composite material according to any one of claims 1 to 6, characterized in that: The polyamide composite material further comprises 0.1 to 10 parts by weight of other additives; Preferably, the other auxiliary agents include at least one of an antioxidant, a lubricant or a heat stabilizer.
8. A method for preparing a polyamide composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The components are mixed and extruded to obtain the polyamide composite material.
9. The preparation method according to claim 8, characterized in that: The mixed material also includes other additives; Preferably, the extrusion temperature is 160-260°C.
10. A silk-screen material, characterized in that: The screen printing material comprises the polyamide composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Graphene nano-silver composite conductive ink and preparation method thereof
CN110776786A
Graphene composite conductive ink and preparation method thereof
CN110862716A
Graphene composite functional electromagnetic shielding film and preparation method thereof
CN113215816A